Історія вивчення археологічних пам'яток Правобережної Київської землі середини XIII-XV ст. - Капустін, К.М. (Археологія, 2011)
Розглянуто історію вивчення археологічних пам’яток Правобережжя Київської землі золотоординського та литовського
часів протягом другої половини ХІХ — початку ХХІ ст. Изучение археологических памятников Киевской земли середины XIII—XV вв. продолжается более 150 лет.
Впервые материалы послемонгольского времени были зафиксированы во второй половине 19 в., в частности в
с. Белогородка Киевской обл. (В. Хвойка). Но позитивные сдвиги в изучении этих древностей наблюдаются в
послевоенное время. В ходе разведок Т.С. Пассек в Поросье, В.К. Гончарова по р. Роставица, Р.И. Выезжева по
р. Тетерев, Н.В. Линки в рамках экспедиции «Большой Киев» зафиксированы культурные слои указаного времени,
а с конца 1940—1950х
гг. значительно активизируются разведки и раскопки на памятниках. Из наиболее интересных
материалов отметим результаты исследований городища и поселения у хут. Половецкий Киевской обл.,
где зафиксированы остатки хозяйственных и жилых построек, собран множественный хозяйственный инвентарь,
оружие, военное снаряжение. Недалеко от поселения располагался могильник, часть погребений которого
можно датировать XIII—XIV вв.
На протяжении 1950—1960х
гг. разведками И.П. Русановой, М.П. Кучеры, Э.А. Сымоновича, О.Н. Приходнюка,
Г.Г. Мезенцевой, С.С. Березанской обнаружены новые, а также уточнена датировка ранее известных памятников
древнерусского и позднесредневекового времени. С средины 1960х
гг. наступает качественно новый
этап исследований Киева, связанный с началом масштабных раскопок Киевской экспедиции под руководством
П.П. Толочка. Материалы золотоордынского и литовского времени зафиксированы на многих участках древнего
Киева и его окраин.
В 1970—1980х
гг. М.П. Кучера выявил значительное количество памятников послемонгольского времени в
Киевской, Житомирской, Черкасской, Черниговской, Полтавской и других областях. Продолжались и изыскания
на территории древнерусских городов. Культурные слои и отдельные объекты середины XIII—XV вв. зафиксированы
в Черкассах, Белой Церкви, Житомире, Малине и, конечно, Киеве.
С конца 1980х
гг. интенсивность и качество исследований на памятниках указанного времени значительно
возрастает. Сплошное обследование территорий Каневского заповедника Черкасской обл., Фастовского рна
Киевской обл. и Овруцкого рна
Житомирской обл. позволило картографировать значительное количество памятников.
В целом за последние 20 лет наблюдается стабильная тенденция к активизации исследований на позднесредневековых
памятниках Южной Руси, что связано с интенсификацией раскопок, в первую очередь, городов
Киевской земли и Киева.
Ныне на территории Правобережья Киевской земли известно 177 памятников средины XIII—XV вв. — поселения,
городища, пещерные комплексы, клады и др. На территории Киева зафиксировано еще 57 пунктов с
материалами послемонгольского времен.
Картографирование памятников показало их наибольшую концентрацию в Киевской обл., наименьшую — в
Житомирской, что связано с состоянием исследования отдельных регионов. Абсолютное большинство памятников
известно исключительно по материалам разведок и сбору подъемного материала. Только поселение у с. Софиевская
Борщаговка исследовано широкой площадью, на некоторых проводились раскопки (Григоровка, Половецкое,
Белая Церковь, Черкассы и др.). Study of archaeological sites of Kyiv land from the middle of the 13th c. to the 15th c. has been continuing for more than 150
years. First materials on postMongolian
period were found in the second half of the 19th c., specifically in Bilohorodka village
of Kyiv Oblast (V. Khvoika). However, the positive improvements in study of the 13th—15th centuries antiquities are seen in the period after the war. During the archaeological prospectings along the Ros River by T.S. Passek, along the Rostavytsya
River by V.K. Honcharov, along the Teteriv River by R.I. Vyezzhev, and by N.V. Linka within the «Great Kyiv» Expedition,
cultural layers of the mentioned period were discovered. Since the end of the 1940s
and 1950s
archaeological prospecting
and excavations have been significantly activated at the sites. Of the most interesting materials one should note the results of
research of a hillfort
and a settlement near Polovetskyi hamlet in Kyiv Oblast where the remains of husbandry and dwelling
structures were found, numerous household inventory, arms, and military munitions were collected. There was a burial ground
not far from the settlement where some of burials can be dated by the 13th—14th centuries.
During the 1950s
and 1960s
new sites were discovered and also the dates of the sites known before were specified after
the archaeological prospecting by I.P. Rusanova, M.P. Kuchera, E.A. Symonovych, O.M. Prykhodnyuk, H.H. Mezentseva,
and S.S. Berezanska. Since the middle of the 1960s
a qualitatively new stage of Kyiv studies started which was related to the
beginning of ample excavation of the Kyiv Expedition directed by P.P. Tolochko. Materials of the Golden Horde and the
Lithuanian periods were found at many areas of ancient Kyiv and its suburbs.
In the 1970s
and 1980s,
M.P. Kuchera discovered a significant number of sites of the postMongolian
period in Kyiv,
Zhytomyr, Cherkasy, Chernihiv, Poltava, and other Oblasts. Studies on the territory of Ancient Rus cities were ongoing.
Cultural layers and separate objects from the middle of the 13th c. to the 15th c. were found in Cherkasy, Bila Tserkva,
Zhytomyr, Malyn, and of course in Kyiv.
Since the end of the 1980s,
rate and quality of research at the Golden Horde and Lithuanian periods sites significantly
increased. Entire study of the territories of Kaniv Preserve in Cherkasy Oblast, of Fastiv Region in Kyiv Oblast, and of
Ovruch Region in Zhytomyr Oblast allowed the scholars to cartography a great deal of sites.
As a whole, in the last 20 years, a stable tendency towards the activation of the research at the Late Mediaeval sites of
the South Rus is seen which is related to the increase of intensiveness of excavations, first of all, at the cities of Kyiv Land
and in Kyiv.
177 sites of the period from the middle of the 13th c. to the 15th c. are known on the territory of the left bank region of Kyiv
Land today: settlements, hillforts,
cave complexes, hoards, etc. 57 more sites with materials of the postMongolian
period
are discovered on the territory of Kyiv.
Cartography of sites showed their highest concentration in Kyiv Oblast and the lowest one in Zhytomyr Oblast, which
is related to the condition of research in separate regions. Absolute majority of sites are known only by the materials of
archaeological prospecting and collecting of surface finds. Only the settlement near Sofiyivska Borshchahivka village was
studied on the broad area, and several settlements were excavated (Hryhorivka, Polovetske, Bila Tserkva, Cherkasy, etc.).